Community Empowerment by Providing Knowledge of The Benefits of VCO (Virgin Coconut Oil) for Health and The Process of VCO Production - Annisa, Istiana; Armal, Hadits Lissentiya; Mahardhika, Rian Bayu (Jurnal Menara Pengabmas, 2023)
VCO (Virgin Coconut Oil) is a processed product from coconuts which is made by physical or methods to produce virgin coconut oil with the characters of low water content and free fatty acids, smells good and has a shelf life of more than 12 months, due to the highest content. VCO (Virgin Coconut Oil) is lauric acid (monolaurin) as much as 32.73% so that VCO has an anti-microbial effect, good for bacteria or fungi. VCO (Virgin Coconut Oil) has good benefits for health and has economic value.Community service activities aim to apply the results of research in the field of health science and technology, especially in increasing knowledge of the benefits of VCO (Virgin Coconut Oil) for health and knowing the process of making VCO (Virgin Coconut Oil). Thus the community is able to process VCO (Virgin Coconut Oil) independently for their own needs and business. The results of the community service activities were the training of 36 residents of RT 016 RW02 Tegalsari Village, Walantaka Serang District - Banten, while the outputs achieved were the publication journals and videos of community service activities.